(untitled) (Journal of Health, Population and Nutrition, 2010)
Despite the national vitamin A and antihelminthic prophylaxis programmes, both intestinal geohelminths and subclinical vitamin A deficiency continue to be prevalent among children in developing countries. Studies on potential synergistic effects of vitamin A supplementation and deworming on retinol status have inconsistent results. The purpose of the present study was to investigate the impacts of low-dose β-carotene supplementation and antihelminthic therapy on serum retinol and β-carotene concentrations in preschool children of Bangladesh. Two hundred and forty-four children, known to be infected with Ascaris lumbricoides, were randomized into four treatment groups: I-IV. Group I and II received two oral doses of 400 mg of albendazole each, the first dose at baseline and the second dose after four months; Group III and IV received placebo in place of albendazole. In addition, Group I and III received 1.2 mg of β-carotene powder in capsule daily for six months, and Group II and IV received placebo in place of β-carotene. Serum retinol and β-carotene levels were measured before and after six months of the interventions. Serum retinol and β-carotene increased significantly in Group I where both antihelminthic therapy and daily β-carotene supplementation were given (p<0.05 and p<0.001 respectively). Antihelminthic therapy alone only improved serum β-carotene concentration (p<0.0001). Low-dose β-carotene supplementation, along with an antihelminthic therapy, synergistically improved vitamin A status. This finding has public-health implications for improving vitamin A status of children in developing countries. Key words: Albendazole; Antihelminthics; Ascariasis; Ascaris lumbricoides; β-carotene; Children; Deworming; Impact studies; Retinol; Vitamin A deficiency; Bangladesh DOI: 10.3329/jhpn.v28i3.5549 J HEALTH POPUL NUTR 2010 Jun;28(3):230-237